Three‐Year Follow‐up of Lanthanum Carbonate Therapy in Hemodialysis Patients. (16th April 2013) - Takeuchi, Kazuhisa; Matsuda, Etsuko; Sekino, Makoto; Hasegawa, Yukiko; Kamo, Yoshie; Kikuchi, Natsue; Sekino, Hiroshi
Abstract: For 3 years following the start of lanthanum carbonate therapy, effects on other pharmaceutical treatment with sevelamer hydrochloride (SH), calcium carbonate (CC), and vitamin D, and those on clinical condition were examined. Dialysis patients with hyperphosphatemia (89 cases; average age 55.2 years; dialysis history of 10 years; 50 male and 39 female), who agreed to start lanthanum carbonate (LC) administration, were observed for a mean period of 32.6 ± 6.2 months. Mean daily dosages of CC and SH before starting LC were 2.68 g and 0.73 g; mean daily dosage amounts of LC, CC, and SH at the time of final evaluation were 0.87 g, 2.30 g, and 0.99 g, respectively. After the application of LC, serum phosphate as well as serum calcium controls were significantly improved, and the amounts of active vitamin D agents applied was significantly increased. In conclusion, LC is useful in managing serum phosphorus levels (P levels), and little incidence of hypercalcemia suggests favorable concomitant use with active vitamin D agents in LC therapy.